A photoactive lysosome targeting RuII complex downregulates stemness genes in oral squamous cell carcinoma. Issue 22 (4th October 2022) - Roy, Souryadip; Mitra, Paromita; Acharya, Sourav; Roy, Shantanu Saha; Ghosh, Shilpendu; Maji, Moumita; Modak, Niladri; Ghosh, Nirmalya; Acharya, Moulinath; Singh, Sandeep; Mukherjee, Arindam
Abstract : Morphocumin coordinated Ru II – p -cymene complex acts as a type-I photosensitizer to inhibit growth of CSC enriched 3D-spheroids of oral squamous carcinoma downregulating stemness genes (cMYC, SOX2, OCT4) with no systemic toxicity to zebrafish embryos in the dark. Abstract : Half-sandwich Ru II –arene complexes with curcuminoids exhibit excellent chemotherapeutic effects but their photoactivity remains unexplored. Here we present a 1, 3-diketone coordinated Ru II –arene complex (1 ) as a type-I photosensitizer (PS) displaying excellent efficacy against cancer stem cell (CSC) enriched oral squamous cell carcinoma (OSCC). The phenolic OH of curcumin functionalized with ethylmorpholine provides stability and adequate lipophilicity to direct L (morphocumin) and 1 towards lysosomes. L and 1 show excellent phototherapeutic index against triple-negative-breast cancer and OSCC cell lines along with the inhibition of the formation of 3D-spheroids of the CSC enriched OSCC cell line SCC070. The CSC enrichment was confirmed by fluorescence-activated single cell sorting (FACS) studies using CD44 as the marker. Complex 1 showed excellent performance against preformed 3D-spheroids ( ca. 60–100 μm) of GFP tagged Notch1 overexpressing SCC070–hICN–GFP and downregulated certain stemness-related genes (cMYC, SOX2, OCT4, ALDH1A1, and ABCG2). cMYC activation in multiple cancers is crucial to sustaining the Warburg effect, so downregulation of cMYC by 1 should significantly affect both the CSCs and bulk cancer cells. In vivo, both L and 1 showed no systemic toxicity to zebrafish embryos in the dark.